Evolution and Dynamics of the Greenland Ice Sheet over Past Glacial-Interglacial Cycles and in Future Climate-Warming Scenarios - GREVE, Ralf
The 5th International Workshop on Global Change: Connection to the Arctic (GCCA5), 15-16 November 2004, University of Tsukuba, Japan